Entrepreneurial Ecosystem: Comparative Analysis of Petrozavodsk and Pskov - Valeriya Grinchenko (Экономическая социология, 2024)
The development of entrepreneurship is a crucial tool for achieving economic growth and enhancing the investment appeal of regions. Many small and medium-sized Russian cities display varied tendencies in economic development, which can be explained by both objective differences in their entrepreneurial ecosystems and how these ecosystems are portrayed in media narratives. This paper presents a comparative analysis of the media representation of entrepreneurial ecosystems in two Russian cities, Petrozavodsk and Pskov. It examines the manifestation and interaction of different types of entrepreneurial ecosystem attributes within these media narratives. The choice of cities for analysis aligns with the objectives of the research project by the ICSER “Leontief Centre”: “Genius Loci and Zeitgeist,” under which this study was conducted. Using corpus-assisted discourse analysis and thematic modeling with LDA, this research examines word frequencies and modeled topics—both common and unique to each locality—and analyzes topic co-occurrence in each city’s discourse. The findings highlight differences and similarities in the media representation of entrepreneurial ecosystems, noting the prevalence of material attributes in both discourses, while also identifying unique interactions among different types of attributes in Petrozavodsk and Pskov. These insights offer a foundation for understanding factors that shape entrepreneurial activities in these regions and suggest directions for future research to empirically examine the relationship between these attributes and local entrepreneurial activity indicators.